Waste management: impact on metal accumulation and speciation in Aba River channel, Nigeria. Issue 1 (2nd January 2021) - Ebong, Godwin A.; Etuk, Helen S.; Dan, Emmanuel U.; Onukwubiri, Margaret A.
ABSTRACT: The impact of indiscriminate disposal of waste materials on the quality of Aba River was examined in this research. Levels of Cd, Pb, Cu, Ni, Fe, Zn, Cr, and Mn were determined in water and sediments from Aba River. Modified BCR sequential extraction procedure was employed for the fractionation of metals in sediments. Levels of toxic metals in water (Cd, Pb, Ni, and Cr) were higher than their recommended limits for potable water. However, mean levels of all the metals except Fe were within their safe limits in sediment. Levels of all the metals in sediments were also higher than in water significantly at p < 0.05. Results showed that Cd, Pb, Ni, and Cr existed mostly in the non-residual fractions while essential elements (Cu, Fe, Zn, and Mn) existed mainly in the residual fraction. Consequently, toxic metals were more mobile and bio-available than the essential ones in Aba River. Cd, Pb, and Ni were metals with serious potential health risk to those exposed to the River. Principal component analysis revealed natural and anthropogenic factors as being responsible for the accumulation of metals in the studied Aba River.